One-step RT-PCR for detection of Zika virus - Faye, Oumar; Faye, Ousmane; Dupressoir, Anne; Weidmann, Manfred; Ndiaye, Mady; Alpha Sall, Amadou (Journal of clinical virology, 2008)
Zika virus (ZIKV) is an emerging mosquito-borne flavivirus circulating in Asia and Africa. Human infection induces an influenza-like syndrome that is associated with retro-orbital pain, oedema, lymphadenopathy, or diarrhea. Diagnosis of Zika fever requires virus isolation and serology, which are time consuming or cross-reactive. To develop a one-step RT-PCR assay to detect ZIKV in human serum. An assay targeting the envelope protein coding region was designed and evaluated for its specificity, detection limit, repeatability, and capacity to detect ZIKV isolates collected over a 40-year period from various African countries and hosts. The assay's detection limit and repeatability were respectively 7.7 pfu/reaction and 100% in serum and L-15 medium; none of 19 other flaviviruses tested were detected. The assay is rapid, sensitive, and specific to detect ZIKV in cell culture or serum, but needs to be validated for diagnosis using clinical samples.